Developments of three mems devices : a microgripper, a micromechanism and a microaccelerometer - Su, Cheng. (2008)
Micro Electro Mechanical systems (MEMS), the combination of micro sensors, micro actuators, and microstructures, is attracting more and more attention all over the world. MEMS technology promises to develop smart products that are of low cost, small size and high performance.